Tradisi Jamu Laut menjadi Sistem pada Masyarakat Desa Jaring Halus - Daniel Fernando Hutapea; Bahrul Khair Amal (Mahesa Research Center, 2018)
This study aims to find out the Jamu Laut Tradition carried out by the Jaring Halus Village community, and to know the values in the tradition. The problem is how the tradition of sea jamu is carried out by the local community and the values in the tradition become a system of belief. For this reason, the AGIL Talcot Parson theory is used and the method used is a qualitative method, a survey conducted by conducting interviews with informants. This research was conducted in the village of Jaring Halus, Secanggang District. The results of this study are that the tradition is still carried out according to the instructions of the sea handler who can wangsit through the dream. Only the execution time has changed, which once was once a year to once every three years. Even so, the values that exist in the tradition of herbal medicine are well preserved like family values. This tradition has remained until now despite the progress of the times. Likewise human relations with nature are maintained so that there is symbolic mutualism between humans and nature.